Silat Cekak Malaysia: a pathway to empowering women through tradition, discipline, and holistic development - Ahmad Zawawi, Azlyn (Universiti Teknologi MARA, Kedah, 2025)
Silat Cekak Malaysia (or Silat Cekak), a traditional Malay martial art, is not just a method of self-defense but a dynamic framework for physical, mental, and spiritual empowerment. Originating from Kedah, Silat Cekak has its roots in Malay history, evolving from the era of pre- Langkasuka grandeur through the challenges of Thai imperialism in 1821. Beyond its historical significance, Silat Cekak integrates practical techniques with cultural and spiritual values, providing women with a powerful pathway to self-discovery and resilience. Its profound impact is evident in the ways it blends historical legacy, practical application, mental fortitude, and spiritual enrichment into a holistic art form (Janudin & Yusoff, 2021).